Teachers’ Perceptions and Strategies in Promoting Reading Literacy at State Madrasah Ibtidaiyah - Karim Karim; La Ode Adhi Virama; Reski Nursyawal; Risman Iye (Journal Evaluation in Education (JEE), 2025)
Purpose of the Study: This study aims to identify teachers’ perceptions of reading literacy and the strategies used to enhance literacy skills at State Madrasah Ibtidaiyah in Baubau City. Methodology: The research employs a qualitative approach using a phenomenological method to explore teachers’ views and experiences. Data were collected through observations, semi-structured interviews, and document analysis. Instruments used include interview guides, observation sheets, and document analysis formats. Data analysis was conducted interactively through data reduction, data presentation, and conclusion drawing. Main Findings: The study finds that teachers hold diverse perceptions of reading literacy, ranging from basic technical reading skills to deep critical comprehension. Strategies such as the phoneme-grapheme approach, group discussions, and project-based learning are adapted to suit different grade levels. Key challenges include a lack of reading materials, insufficient support from the family environment, and inadequate school policies on literacy. Nevertheless, the use of interactive and collaborative strategies has enhanced students’ critical thinking, especially in interpreting religious texts. Novelty/Originality of this Study: This study provides a contextual understanding of how teachers at Islamic elementary schools in regional Indonesia perceive and approach reading literacy. It underscores the integral relationship between teacher perception, pedagogical strategy, and environmental factors in cultivating a literacy culture especially in religious education contexts where critical reading plays a vital role.